RELATIONSHIPS RELATIONSHIPS SUPPORT THE HUSBAND WITH THE EARLY DETECTION OF CERVICAL CANCER AGE COUPLES ON IVA METHOD IN CLINICS KOM YOS SUDARSO PONTIANAK - Lestari Makmuriana; Vivi Indah Lestari; Parliani Parliani; Lilis Lestari (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2022)
Abstract The World Health Organizations (WHO) year 2013, there are 493,243 inhabitants per year new cervical cancer sufferers with mortality found as much as 273,505 soul per-tahun. Cervical cancer is rare in young women aged under 20 years, amounting to 50% found in women aged 35-55 years, 50% again in women who are under 35 years of age. Purpose: This research aims to know the relationships support the husband with the early detection of cervical cancer age couples on IVA method lush. Methods: The methods used in this research is quantitative research with correlative analytic approach that uses cross sectional. Sampling is done using the technique of sampling with the number of consecutive samples of 140 people. Data collection using the questionnaire with the data analysis using chi square test. Results: The results of this research show that there is a relationship between support with detsksi husband early cervical cancer age couples on IVA method in Clinics Kom Yos Sudarso Pontianak with a p value of 0.009 (p value < 0.05), OR = 2.64. Conclusions: The conclusion is the husband's support given can make his wife IVA checks for cervical cancer prevention. Therefore, it is expected to support the husband should be given to the wife of the couple's fertile age with the aim of preventing cervical cancer and reduce the mortality rate of cervical cancer which annually has increased. Keywords : Cervical Cancer, Methods IVA, Support The Husband